Performance Analysis of a Compressor Rotor Dedicated to Low-Power Drive Systems - Natalia Kapela; Karolina Wyżkiewicz; Andrzej Frąckowiak (Energies)
This study investigates the efficiency evaluation of a compressor rotor designed for drive units requiring compressors with a power demand of less than 30 kW. The primary aim of the research presented in this article is to assess the feasibility of utilizing axial compressors to maintain high efficiency across a broad range of rotor speeds. A critical challenge in the considered power range is the occurrence of low Reynolds numbers, specifically those below 250,000. This research seeks to identify the underlying causes of efficiency degradation at low Reynolds numbers and determine the rotor’s geometric parameters which most significantly influence the localized efficiency drop. Compressor efficiency was evaluated through numerical simulations. The numerical model was validated using experimental data and subjected to a grid independence study. Simulations were conducted for nine geometric configurations of the axial compressor rotor, with modifications to parameters such as the blade angle, blade thickness, blade solidity, and hub-to-tip ratio. For each configuration, a series of simulations was performed at rotor speeds ranging from 400 RPM to 2400 RPM. The simulation results indicated that the blade angle solidity was the most influential parameter affecting efficiency. A reduction in the blade angle led to approximately a 20% decrease in efficiency, primarily due to localized flow separation near the blade tip. Additionally, altering the number of blades caused a 20% efficiency reduction attributed to hub corner separation. The findings enabled the identification of optimal parameters, which will serve as a foundation for efficiency testing in the multistage configuration.